Microstructure and Wear Resistance of an Arc-Sprayed Fe-Based Coating after Surface Kemelting Treatment - Tian, H.L.; We, S.C.; Chen, Y.X.; Tong, H.; Liu, Y.; Xub, B.S. (Проблемы прочности, 2014)
The aim of the study was to improve the lamellar structure and wear resistance of arc-sprayed coatings. FeNiCrAl arc-sprayed coatings were remelted by the tungsten inert gas welding method. The as-sprayed and remelted specimens were subjected to comparative structural phase composition examination using optical microscopy, scanning electron microscopy and X-ray diffraction. Additionally, the effect of the remelting treatment on the wear mechanism of the arc sprayed coatings was also studied. It was found from the experiments that the tungsten inert gas surface process has the potential to form pore- and crack-free coatings. Further investigations showed that the dominant mechanism of wear for the as-sprayed coatings was oxide delamination and for the tungsten inert gas remelted coatings was cutting and ploughing